2009
DOI: 10.1128/jvi.02154-08
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Fitness Cost of the M184V Mutation in Multidrug-Resistant Human Immunodeficiency Virus Type 1 in the Absence of Lamivudine

Abstract: Lamivudine therapy selects for the M184V mutation. Although this mutation reduces the replicative capacity of human immunodeficiency virus in vitro, its impact on viral fitness in vivo has not been well defined. We used quantitative allele-specific PCR to precisely calculate the fitness differences between the mutated M184V virus and one that had reverted to the wild type in a cohort of patients by selectively interrupting reverse transcriptase inhibitor therapy, and we found that the M184V variants were consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
68
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 22 publications
4
68
0
Order By: Relevance
“…The relatively rapid decay of HIV-1 VCV resistance in this individual was most consistent with the reemergence of sensitive virus from a preexisting variant rather than the back mutation of multiple V3 loop amino acid substitutions (23,40). Deep sequencing confirmed that the dominant week 48 V3 loop sequence was present as a minor variant in the week 0 plasma sample.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…The relatively rapid decay of HIV-1 VCV resistance in this individual was most consistent with the reemergence of sensitive virus from a preexisting variant rather than the back mutation of multiple V3 loop amino acid substitutions (23,40). Deep sequencing confirmed that the dominant week 48 V3 loop sequence was present as a minor variant in the week 0 plasma sample.…”
Section: Discussionmentioning
confidence: 63%
“…The sampling of more time points during these weeks would have permitted an exact quantification of the total plateau time, as well as a precise determination of the start of resistance decay. The persistence of resistant viruses in plasma for several weeks after drug discontinuation has been observed in patients infected with NRTI-and enfuvirtide-resistant viruses (31,40). The maintenance of a less fit viral variant in plasma, followed by the rapid extinction of this variant, may reflect the time interval between drug discontinuation and the stochastic activation of a cell or cellular population that harbors the archived wild-type viral variant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations